Improving the Public Expenditure Outcomes of the National Rural Employment Guarantee Scheme through Social Accountability Interventions in Sirohi District, Rajasthan, India - Patel, Darshana; Shah, Parmesh; Chakrabarti, Poulomi; Arya, Om Prakash; Cheriyan, George; Agarwal, Sanjay (World Bank, Washington, DC, 2016)
The National Rural Employment Guarantee Act (NREGA), enacted by the government of India in 2006, recognizes employment as a universal legal right for every rural household. Breaking from earlier employment schemes and development programs, NREGA is significant in that it is 'a regime of rights' for poor rural communities. NREGA provides a comprehensive set of entitlements that not only outline judicially enforceable terms for employment but also give citizens a central role in all stages of implementation. The overall objective of this social accountability intervention was to assess NREGS implementation, identify lacunae in program implementation, and build ownership of the findings of this intervention within all levels of government. NREGS has a system of continuous external monitoring and verification to curb corruption and maintain quality implementation. The Citizen Report Card (CRC) survey found that 56 percent of the project worksites were visited fewer than three times by upper level government authorities.